Prior Puma Lentivirus Infection Modifies Early Immune Responses and Attenuates Feline Immunodeficiency Virus Infection in Cats - Wendy S. Sprague; Ryan M. Troyer; Xin Zheng; Britta A. Wood; Martha Macmillan; Scott Carver; Susan VandeWoude (Viruses, 2018)
We previously showed that cats that were infected with non-pathogenic Puma lentivirus (PLV) and then infected with pathogenic feline immunodeficiency virus (FIV) (co-infection with the host adapted/pathogenic virus) had delayed FIV proviral and RNA viral loads in blood, with viral set-points that were lower than cats infected solely with FIV. This difference was associated with global CD4+ T cell preservation, greater interferon gamma (IFN-γ) mRNA expression, and no cytotoxic T lymphocyte responses in co-infected cats relative to cats with a single FIV infection. In this study, we reinforced previous observations that prior exposure to an apathogenic lentivirus infection can diminish the effects of acute infection with a second, more virulent, viral exposure. In addition, we investigated whether the viral load differences that were observed between PLV/FIV and FIV infected cats were associated with different immunocyte phenotypes and cytokines. We found that the immune landscape at the time of FIV infection influences the infection outcome. The novel findings in this study advance our knowledge about early immune correlates and documents an immune state that is associated with PLV/FIV co-infection that has positive outcomes for lentiviral diseases.